Venda Sexy: unofficial memories of a detention center - Arellano Hermosilla, Claudia (2020)
The following article reflects on the memories and stories of women who were survivors of the Centro de Detención y Tortura la Venda Sexy (Venda Sexy Detention and Torture Center), of the Directorate of National Intelligence (DINA), during the military dictatorship in Chile.  This precinct, in particular, exacerbated the repression, inclined towards sexual political violence. Within these extremely repressive conditions there existed instances of resistance and sorority among women, which allowed them to bend that historical wound, towards an assemblage process, which has translocated to the current feminist struggle.